Performa Segmenting Targeting Dan Positioning Untuk Mempertahankan Mind Share Pada Produk Bolu Kering Mak Plengeh UD Wahyu Jaya Kota Kediri - Lestari, Ericha Puspha Ayu; Aliami, Sri; Leksono, Poniran Yudho (Efektor, 2022)
The company's competition not only focuses on the marketing mix but must exist to show the formulation of strategic innovations. Mak Plengeh's dry cake is a superior product of UD Wahyu Jaya Kediri; appropriately apply segmenting, targeting, and positioning (STP) strategies to maintain mind share. This study aims to determine the performance of STP to keep the mind share of Mak Plengeh dried sponge products. The research used a descriptive qualitative approach. They collect data through observation, interviews, and documentation. They checked the validity of research findings using source triangulation. The results: (1) Segmenting includes: Kediri and Surabaya, aged 5-70 years, both male and female, alpha generation to baby boomers, the lower middle class, consumptive, like snacks, consumed by individuals and various events, consumers feel satisfied and make repeat purchases, teenagers order online while adults go offline (2) Targeting, distributors and packaging are a relatively large and profitable market segment, recruiting office employees who have skills, while the production department is inexperienced, the smiling character is a power of differentiation, the company provides training, briefings, and routine performance evaluations, consistently innovate its products, has a large production volume, provides good service, and is consistent with quality. (3) Positioning by providing testers, licensing information, and materials used so products can be purchased anywhere and responsive to the market.